Een postkoloniale spagaat : Een publieke rede in de VN en een geheim telex¬bericht Albert Helman als diplomaat - van Kempen, Michiel (Acta Neerlandica, 2020)
Albert Helman, pseudonym of Surinamese Lou Lichtveld (1903-1996), was a prominent writer of the Dutch-Caribbean. Around 1960 he decided to opt for a job as a diplomat at the Netherlands embassy in Washington and the United Nations in New York. Since his native country, Suriname, was still a part of the Netherlands, it could not lead its own foreign policy. Lichtveld advised the government in Suriname, but worked along the lines of the Foreign Department of The Netherlands in The Hague. This position was extremely complicated: we see him struggling with his loyalties when he has to present the Dutch standpoint in the UN in the case of the apartheid-policy in South-Africa.